2012
DOI: 10.1177/0192623311431466
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Stromal Polyps in Rodents: Biology, Etiology, and Relevance to Disease in Women

Abstract: Endometrial stromal polyps (ESP) are a common spontaneous reproductive tract lesion in the female rat. However, there is limited information concerning the etiology, biology, and significance of these polyps as an end point in toxicology and carcinogenicity studies. This paper reviews relevant literature to address these aspects of ESP with respect to potential relevance to human uterine tumors. Endometrial stromal polyps in rodents appear as age-related lesions. There are only a few chemicals tested for carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…When we evaluate these FN substances histopathologically, 77 of the 96 FN substances appeared to induce benign tumors or benign and malignant tumors, which are considered not relevant for the human situation ( 36 ): acinar pancreatic tumors and islet cell neoplasia ( 36 ); pheochromocytomas of the adrenal medulla ( 64 ); forestomach tumors ( 65 , 66 ); hepatocellular tumors induced by peroxisome proliferators ( 48 , 67 – 69 ); fibroadenomas of the mammary gland ( 70 ); pituitary tumors (adenohypophysis tumors) ( 71 ); Leydig cell (interstitial cell) tumors of the testes ( 72 , 73 ); thyroid follicular cell tumors ( 74 76 ); and urinary bladder tumors ( 75 , 77 80 ) and uterus tumors (endometrial stromal polyps) ( 81 ). That means that 19 FN substances still remain using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluate these FN substances histopathologically, 77 of the 96 FN substances appeared to induce benign tumors or benign and malignant tumors, which are considered not relevant for the human situation ( 36 ): acinar pancreatic tumors and islet cell neoplasia ( 36 ); pheochromocytomas of the adrenal medulla ( 64 ); forestomach tumors ( 65 , 66 ); hepatocellular tumors induced by peroxisome proliferators ( 48 , 67 – 69 ); fibroadenomas of the mammary gland ( 70 ); pituitary tumors (adenohypophysis tumors) ( 71 ); Leydig cell (interstitial cell) tumors of the testes ( 72 , 73 ); thyroid follicular cell tumors ( 74 76 ); and urinary bladder tumors ( 75 , 77 80 ) and uterus tumors (endometrial stromal polyps) ( 81 ). That means that 19 FN substances still remain using this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with B6C3F1 mice showed that TMPTA increased the relative length of estrous stages in female mice (National Toxicology Program, 2005). Although the contribution of hormones is not clearly shown in rodents, development of stromal polyps in rodents is usually associated with aging (Davis, 2012). In humans, the peak incidence of uterine sarcomas is between 50 and 65 years of age (Seddon and Davda, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Stromal polyps are considered a common background lesion in many strains of rats and their occurrence is thought to coincide with natural estrous cycle deregulation in rats and prolonged progesterone stimulation (Leininger and Jokinen, 1990). Conversely, others have suggested that rodent stromal polyps are not hormone sensitive (Davis, 2012). In the current study, there was evidence that exposure to p-chloro-α,α,α-trifluorotoluene for 3 months resulted in estrous cycle alterations in female rats and mice.…”
Section: Not For Attribution Camera Draftmentioning
confidence: 99%